(untitled) (Journal of Engineering, 2010)
The stresses and deflections in robot arm was analyzed using ANSYS software package. Industrial robot analyzed in this work consists of three arms that have 2-DOF. The analysis of each arm had been made separately. The maximum stress and deflection have been analyzed for a static applied at one end of the arm while has the other end fixed. Links of various cross-sections having same masses, length, and material properties to make a choice of the shape that gives a high stiffness to weight ratio have been examined. After specifying the best section for the arms of the robot an optimization process began to determine the dimensions of the arms sections which give the least deformation this had been done by the aid of a program build up by using the MATHCAD software package. In the beginning the program finds the optimum section in which the stress in the members not exceeds the allowable stress and finds the total weight of the robot after that the program begins to change the dimensions to satisfy the condition of minimum deflection of the whole robot after that the program estimates the best choices of the dimension for each section that gives the minimum weight and deflection. The dynamic behavior of the best chosen structure of industrial robot was studied to find the natural frequencies ( n w ) and mode shapes. The result shows that the hollow circular section is the best section for the first link while a square section is the best section for the other two links.